ChemInform Abstract: I2‐Catalyzed Oxidative Cross‐Coupling of Methyl Ketones and Benzamidines Hydrochloride: A Facile Access to α‐Ketoimides. Issue 48 (2nd December 2014) - Wu, Xia; Gao, Qinghe; Liu, Shan; Wu, Anxin
Abstract This iodine catalyzed oxidative amidation is advantageous with regards to operational simplicity, metal‐ and peroxide‐free conditions, and high yields.